The Influence of Experiential Marketing and Islamic Branding on Word of Mouth and The Decision of Choosing a Private College - Daisy Aulia Fitri (PT SOLUSI EDUKASI BERDIKARI, 2025)
This research aims to test and analyze the influence of experiential marketing and Islamic branding on word of mouth and the decision to choose a private university. The research approach used in this study is quantitative. This study's collection technique was distributing questionnaires online via google forms to 200 respondents. The method used in this study is PLS-SEM using SmartPLS software. The results of this research are experiential marketing has a positive and significant effect on college decisions, islamic branding has a positive and significant effect on experiential marketing, experiential marketing has a positive and significant effect on word of mouth, islamic branding has a positive and significant effect on word of mouth, islamic branding has a positive and significant effect on college decisions, word of mouth has a positive and significant effect on college decisions, the role of word of mouth can be a mediator in the relationship between experiential marketing and college decisions and word of mouth can be a mediator in the relationship between islamic branding and college decisions.